EMERGING SCOPE FOR FUNCTIONAL FOODS- GLOBAL APPROACH - DR. D. THYAGARAJAN; M. BARATHI; S. EZHIL VALAVAN (International Journal of Pharma and Bio Sciences, 2013)
Foods or food ingredients that provide a health benefit beyond normal nutritional effects through modulation of specific target functions are generally known as functional foods. All foods are functional to some extent as they provide taste, aroma, nutrients required for normal metabolism, growth and maintenance. However, foods are now being examined intensively because of latest trend towards preventive health care for added physiological, psychological and specific health benefits, which may reduce chronic disease risk and optimize health. Nutrients, herbals, fish, meat, dairy products and dietary supplements are major constituents of functional foods. India is the home of a large number of medicinal herbs, spices and tree species that have a substantially large domestic market with lesser foreign competitors at present. Over a long period, there were no strict pharmaceutical regulations on Ayurvedic and nutraceutical products in India. In the present scenario, nutraceuticals and functional foods industries have grown in to multi-million dollar industries. It is estimated that Canadian functional food industry is likely to grow up to 50 billion US dollars. Japan is reported to have the second largest functional food and neutraceutical markets in the world.